Italian Translation, Cultural Adaptation, and Validation of the Toileting Habit Profile Questionnaire Revised (THPQ-R) in Typically Developing Children: A Cross-Sectional Study - Martina Ruffini; Anna Berardi; Anna Benvenuti; Isabelle Beaudry-Bellefeuille; Marco Tofani; Giovanni Galeoto; Donatella Valente (MDPI AG, 2022)
The Toileting Habit Profile Questionnaire Revised (THPQ-R) identifies sensory integration issues in children with defecation problems. Sensory integration issues are recognized as a factor linked to some defecation disorders and identifying such issues is needed to guide the development of an appropriate intervention. The aim of this cross-sectional study was to translate, culturally adapt, and validate the THPQ-R in a population of typically developing (TD) Italian children by measuring its internal consistency and cross-cultural validity. The translation and cultural adaptation were performed according to international guidelines. The questionnaire was administered to the caregivers of TD children, and the analysis was performed on data obtained from 118 TD children. The construct validity of the scale was calculated through the exploratory factor analysis that indicated two factors; Cronbach's alpha was calculated for internal consistency and showed a value >0.7, demonstrating good internal consistency. Cross-cultural validity was also analyzed and showed higher levels of defecation problems at age 5 years. Italian occupational therapists now have a tool to assess possible sensory issues linked to defecation disorders in children aged 3 to 6 years, which may promote more effective clinical practice in this area. Moreover, it will be possible to compare the results obtained from studies conducted in Italy with those conducted in other countries.